ANALISIS PEMAHAMAN DAN HARAPAN WAJIB PAJAK ORANG PRIBADI UMKM - Ponggalo, Rassidaud Tito; Ramananda, Dimaz; Damayanti, Theresia Woro (Politeknik Negeri Jakarta, 2024)
This research aims to demonstrate the understanding and expectations of Micro, Small, and Medium Enterprises (MSMEs) individual taxpayers regarding the implementation of Law No. 7 of 2021 concerning Non-Taxable Income (PTKP). This study is a qualitative descriptive case study conducted using a questionnaire method. The research sample consists of MSME owners in Bekasi Regency who have active Taxpayer Identification Numbers (NPWP) and have been operating for the past three years to ensure informants are aware of changes in MSME tax regulations. The researcher used data such as age, gender, highest education level, and years of business operation for analysis. The research results indicate that the understanding and expectations of individual MSME taxpayers regarding the implementation of Law No. 7 of 2021 concerning PTKP are generally quite good. Factors such as age, highest education level, and years of business operation have an influence on the level of understanding of MSME taxpayers.